Challenges In Assuring Quality In Advanced Therapy Medicinal Products: Cell, Gene, Tissue-Based Therapies, And Organoids With Emerging Mass Spectrometry Approaches - V Fafal, Aarti; D Patel, Bhoomi; Rathi, Sanjesh (Journal of Neonatal Surgery, 2025)
Advanced Therapy Medicinal goods (ATMPs) a branch of modern biomedicine act as a boon for the treatment of previously incurable diseases via revolutionizing modern biotechnologically engineered medicine such as Cell-based therapies, gene therapies, tissue-engineered goods, and developing organoid systems. These technologies have shown extraordinary therapeutic significance, from gene replacement therapy in neurology to CAR-T cells in oncology and bioengineered grafts in regenerative medicine. Quality assurance is confronted with unprecedented challenges because to its complexity, reliance on live materials, and patient variability. Unlike conventional small-molecule pharmaceuticals, ATMPs are neither solely defined by their chemical structure or a single crucial qualitative characteristic. Dynamic biological characteristics like cell viability, differentiation potential, vector integrity, scaffold mechanics, and organoid functionality all affect how well they work as medicines. Although they offer crucial information, traditional analytical methods such as flow cytometry, Enzyme-Linked Immunosorbent Assay (ELISA), Polymerase Chain Reaction (PCR), and histology are frequently reductionist, damaging, or unable to capture the multifaceted state of these treatments. This restriction emphasizes the necessity of sophisticated characterisation technologies. High- resolution and multi-omics analysis in proteomics, metabolomics, glycomics, lipidomics, and imaging applications are made possible by Mass Spectrometry (MS), which has become a potent tool. These methods provide previously unheard-of insight into molecular fingerprints that are directly related to reproducibility, safety, and potency. In this review, the types and characteristics of ATMPs are examined, key quality assurance difficulties are identified, and innovative MS techniques are discussed to close the gaps. By combining robust quality frameworks with state- of-the-art analytical tools, the field can ensure that ATMPs reach their transformative promise while maintaining the highest standards of patient safety and treatment dependability..